Memory and event-related potentials for rapidly presented emotional pictures - Versace, Francesco (2010)
Dense array event-related potentials (ERPs) and memory performance were assessed following rapid serial visual presentation (RSVP) of emotional and neutral pictures. Despite the extremely brief presentation, emotionally arousing pictures prompted an enhanced negative voltage over occipital sensors, compared to neutral pictures, replicating previous encoding effects. Emotionally arousing pictures were also remembered better in a subsequent recognition test, with higher hit rates and better discrimination performance. ERPs measured during the recognition test showed both an early (250–350 ms) frontally distributed difference between hits and correct rejections, and a later (400–500 ms), more centrally distributed difference, consistent with effects of recognition on ERPs typically found using slower presentation rates. The data are consistent with the hypothesis that features of affective pictures pop out during rapid serial visual presentation, prompting better memory performance.